Which attitudes will make us individually and socially happier and healthier? A cross-culture and cross-development analytical model - Fabio Zagonari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
This paper describes a dynamic system for the interrelationships between happiness and health that considers three main attitudes to life: α, β, and γ for Aristotelian, Epicurean, and Stoic, respectively. All variables that have been shown by empirical and theoretical studies to affect individual health and happiness are included (i.e., employment, occupation, education, ethical freedom, equity in achievements). Three main approaches are considered: behavioural and statistical ex-ante, and ex-post behavioural. I develop the model to rank the three attitudes in terms of health for a given happiness level, and consequently, provide insights into which attitude should be adopted by each individual, according to their characteristics: individuals in Protestant and non-Protestant Christian societies should adopt β and γ attitudes, respectively; educated individuals should adopt a γ attitude; and poor individuals should adopt an α attitude. Based on this analysis, I provide insights into which attitude actually is adopted by each society by comparing predicted health and achievement levels with the observed life expectancy at birth and per capita gross domestic product levels in 107 countries, thus providing an empirical test of the analytical model. This analysis revealed a prevalence of β attitudes in Protestant Developed Countries, with larger γ shares in less income-unequal countries; a prevalence of γ attitudes in non-Protestant Christian Developed Countries, with larger β shares in more income-unequal countries; a prevalence of α attitudes in Muslim Less Developed Countries, with larger γ shares in more educated countries; and a prevalence of β attitudes in more educated atheist and Jewish countries.
Keywords: I1; I3; Z1; 330